2021
DOI: 10.1177/15280837211029048
|View full text |Cite
|
Sign up to set email alerts
|

The study of hydrophobicity and oleophilicity of 3D weft-knitted spacer fabrics integrated with silica aerogels

Abstract: The interest in multifunctional textile materials has been increased due to the health and safety measures of living beings, especially in severe conditions. Therefore, this study investigated the hydrophobicity, oil sorption capacity, and bending properties of untreated or uncoated and treated or coated 3D weft-knitted spacer fabric samples (92% polyester/8% spandex), i.e. sample 1, sample 2, and sample 3, having thicknesses of 2 mm (300 gm−2), 3 mm (350 gm−2), and 4 mm (540 gm−2), with silica aerogels (SAs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…The spectra were recorded at the wavenumber range of 400–4000 cm −1 using the attenuated total reflection (ATR) technique. 23 The test was used in 64 scans with 8 cm −1 resolution. The morphologies of samples were observed by scanning electron microscope (FLEX SEM1000, Hitachi, chuocho, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra were recorded at the wavenumber range of 400–4000 cm −1 using the attenuated total reflection (ATR) technique. 23 The test was used in 64 scans with 8 cm −1 resolution. The morphologies of samples were observed by scanning electron microscope (FLEX SEM1000, Hitachi, chuocho, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The surface tension of those liquids is given in Table 2. 23,24 The contact angle was obtained 15 s after placing the droplets on the fabric surface. 25…”
Section: Methodsmentioning
confidence: 99%
“…The existence of Si-O-Si network constructions in the treated 3D WKSFs offered thermodynamic motion from inside to outside and the creation of a homogenous SiO 2 aerogel coating induced constant material distribution on the fabric surface, resulting in decreased surface energy and increased surface roughness, thus, enhanced the hydrophobic and oleophilic properties of the treated samples. 63,71,72 Chemical interaction of untreated and treated 3D weft-knitted spacer fabrics…”
Section: Morphological Properties Of the 3d Weft-knitted Spacer Fabricsmentioning
confidence: 99%
“…[58][59][60][61][62] By using several precursors, co-precursors, and silylating agents with SAs coating, the surface roughness, and specific surface area can be increased, and the surface energy can be decreased, potentially improving the hydrophobicity and oleophilicity of 3D WKSFs. [63][64][65][66][67] Nowadays, the production of hydrophobic and oleophilic surfaces using the sol-gel method has received much interest and has been used widely in many researches. 68,69 No research work has been found between different concentrations of SAs and 3D WKSFs for water-repelling and oil-absorbing materials with reusability properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation